Caries risk assessment in dental practices by dentists from a Brazilian community - TAGLIAFERRO, Elaine Pereira da Silva [UNESP]; da SILVA, Silvio Rocha Correa [UNESP]; ROSELL, Fernanda Lopez [UNESP]; VALSECKI JUNIOR, Aylton [UNESP]; RILEY, Joseph Leo; GILBERT, Gregg Hewit; GORDAN, Valeria Veiga (FapUNIFESP (SciELO), 2020)
Data on dental practices related to caries risk assessment (CRA) are scarce among Brazilian dentists. This study aimed to determine the prevalence of CRA use by dentists and factors associated with its use, as well as to quantify dentists’ ratings of the importance of specific factors when treatment planning. Dentists registered at the Regional Council of Dentistry of Sao Paulo State - Araraquara region were sent two paper questionnaires that comprised: a) characteristics of dentists themselves, their practices, and their patients; and b) the translated version of the “Assessment of Caries Diagnosis and Caries Treatment” Questionnaire from the U.S. National Dental Practice-Based Research Network. Participants were 206 dentists who currently practiced in Araraquara and treated dental caries. Descriptive statistics and multiple logistic regression analyses were used for data analysis. Thirty-six percent of the dentists reported they perform CRA and, among them, 36% indicated they record the assessment on a special form that is kept in the patient chart. More years since dental school graduation (OR = 1.1, p = 0.002) and holding an advanced academic degree (OR=2.6, p=0.005) were associated with a higher likelihood of performing CRA, whereas exclusively using a private practice model (OR = 0.5, p = 0.016) was associated with a lower likelihood of performing CRA. The current oral hygiene and commitment to return for follow-up were the most important risk factors for treatment planning. In conclusion, CRA was not a routine procedure in daily practice among the majority of participating dentists. Specific demographic, practice and academic education characteristics were associated with performing CRA.
Keywords: Dental Caries; Dentists’; Practice Patterns; Risk